Da identificação da crise ao recomeço : itinerário terapêutico de homens transgêneros da Baixada Cuiabana/MT - Porto, Rayssa Karla Dourado (2020)
The biological sex of children occupies a central place in their first interpersonal and subjective relationships, all imaginary and idealized construction of parents is based on this aspect. Even before the children perceive themselves as subjects, cis-heteronormative society dictates that there must be consonance between biological sex, sexual orientation and gender identity. Gender is constructed through the processes of socialization and culture. Thus, gender and subsequently, identity are built in a fluid and constant context. The aim of this study was to analyze the therapeutic itinerary that transgender men take when deciding to enter the transsexualizing process. This is a qualitative research, in which, through individual interviews with a semi-structured script, and a field diary, sought to understand the health care paths that men take. The study population was selected using the Snow Ball technique, and consists of the interview of seven participants who are living in the Baixada Cuiabana cities during the period from June to September 2019. In the process of analyzing the therapeutic itinerary, we chose to work with the crisis phases (Identification, Experience of the crisis, Rupture and the Restart) as described by MALUF (2003). The internet was identified as a field where the subjects find support, indication of professionals, negotiation of prescriptions and medications, therefore it is configured as one of the main spaces for social interaction in the subjects' itinerary. It was observed that the course of the subjects in search of the transsexualizing process is carried out based on the available resources, both financial and access to information and health services. It was revealed that the path of the interviewed subjects is composed of difficulties and related barriers in the access to health services, such as transphobic situations, from the refusal to attend them, to the delegitimization of trans identity. It is concluded that regardless of the demand for the construction of an outpatient clinic aimed at the trans population, the subjects find alternatives to transform their bodies according to their desires and financial conditions, making autonomy in choices prevail.